Planning for a sustainable city region? Regional district heating in Stockholm - Dick Magnusson (European Regional Science Association (ERSA), 2010)
Stockholm is by far the largest city in Sweden and it is also the only region with legislated regional planning. Since the region has the highest and most dense population, regional cooperation is important in many aspects, for example by finding regional solutions for the infrastructure and for energy systems. By cooperating to create regional supply systems it is possible to create more robust and ecologically and economically sustainable systems that use the land as efficiently as possible. An example of such cooperation is the regional district heating systems in the region. The energy consumption for heating and hotwater in buildings is a major share of the Swedish energy balance, and in Stockholm 13 of 55 annual TWh energy use is consumed by district heating. Great potential for climate friendly solutions therefore lie in the system. The individual district heating systems have gradually been interconnected and through these interconnections a better optimized system can be created where peak loads can be evened out, and thus using less fossil fuel. District heating's economies of scale can be used advantageous and makes it possible to build combined heat and power plants for more efficient and environmentally friendly energy production. However, such development does not happen by itself. The municipalities in Sweden have planning monopoly so the creation of a regional energy system requires a shared vision and long-term planning. The aim of this study is therefore to study and compare the municipalities' comprehensive plans from a regional perspective regarding district heating. By studying Stockholm region's 26 municipalities' comprehensive plans between 1978 and 2009, and comparing these with the regional plans, it is possible to understand of their perception of the importance of regional cooperation regarding energy systems and district heating. Furthermore, the aim is to study how the view towards energy and district heating has changed over the time period chosen. What general differences between the municipalities can be seen, how does this change over time and how can this be explained?
Keywords: 330